KOMIK SEBAGAI MEDIA KOMUNIKASI VISUAL PEMBELAJARAN - Dwi Waluyanto, Heru (Institute of Research and Community Outreach - Petra Christian University, 2005)
Visual Communication Design students should be able to think creative and communicate through visual. This two things are important during the process of creating a design. Students should be empowered their creative ability%2C but also they should be eased in the way they study. Comic as a media for learning is one alternative which is functioned to solve the problems above. Abstract in Bahasa Indonesia : Mahasiswa desain komunikasi visual dituntut mampu dan terbiasa berpikir kreatif serta berkomunikasi secara visual. Kedua hal ini sangat penting peranannya dalam proses penciptaan karya desain. Untuk itu%2C mahasiswa perlu diberdayakan kemampuan kreatifnya namun juga dimudahkan dalam cara belajarnya. Komik pembelajaran merupakan alternatif yang berfungsi untuk memecahkan masalah tersebut di atas. creativity%2C learning comic.